Suicide, Stigma and COVID-19: A Call for Action From Low and Middle Income Countries - Shoib, Sheikh; Chandradasa, Miyuru; Saeed, Fahimeh; Armiya’u, Aishatu Yusha’u; Roza, Thiago Henrique; Ori, Dorottya; Jakhar, Jitender; Rodrigues-Silva, Nuno; Banerjee, Debanjan (Frontiers in Psychiatry, 2022)
Suicide is a global health issue that needs to be addressed. The COVID-19 pandemic has resulted in an increased mental health burden. Stigma has obstructed efforts to prevent suicide as individuals who need urgent support do not seek appropriate help. The influence of stigma is likely to grow in tandem with the COVID-19 pandemic. The stigmatisation of persons with mental illnesses is widespread worldwide, and it has substantial effects on both the individual and society. Our viewpoints aim to address the probable link between stigma and suicide in the wake of the current pandemic and propose ideas for reducing suicide-related stigma.